Genome profiling of fluoroquinolone-resistant uropathogenic Escherichia coli isolates from Brazil - da Silva, Patrick [UNESP]; Lustri, Bruna C. [UNESP]; Castilho, Ivana Giovannetti [UNESP]; Ferreira, Adriano Martison [UNESP]; Hernandes, Rodrigo T. [UNESP]; Schembri, Mark A.; Moreira, Cristiano G. [UNESP] (Springer Nature, 2021)
Urinary tract infections (UTIs) are a major public health concern in both community and hospital settings worldwide. Uropathogenic Escherichia coli (UPEC) is the main causative agent of UTI and increasingly associated with antibiotic resistance. Herein, we report the draft genome sequence of 9 fluoroquinolone-resistant UPEC isolates from Brazil and examine selected major phenotypic features, such as antimicrobial resistance profile, phylogroup, serotype, sequence type (ST), virulence genes, and resistance marks. Besides the quinolone resistance, beta-lactams, ESBL production, aminoglycosides, and tetracycline resistance were observed. High prevalence of 20 virulence genes was detected in all isolates, such as those encoding type 1 fimbriae, acid tolerance system, and hemolysin E, particularly within E. coli B2 phylogroup, as ST131 and ST1193 strains, among other genomic analyses as genomic islands, resistance plasmids, and integron identification.
Keywords: Escherichia coli; Fluoroquinolone-resistant; Pathogenesis; UPEC; UTI